Streamwise vortices in shear flows: harbingers of transition and the skeleton of coherent structures - Hall,P; Sherwin,S (J. Fluid Mechanics, 2010)
The relationship between asymptotic descriptions of vortex-wave interactions and more recent work on ’exact coherent structures’ is investigated. In recent years immense in- terest has been focused on so-called self-sustained processes in turbulent shear flows where the importance of waves interacting with streamwise vortex flows has been eluci- dated in a number of papers. In this paper it is shown that the so-called ’lower branch’ state which has been shown to play a crucial role in these self-sustained processes is a finite Reynolds number analogue of a Rayleigh vortex-wave interaction with scales ap- propriately modified from those for external flows to Couette flow the flow of interest here. Remarkable agreement between the asymptotic theory and numerical simulations is found even down to relatively small Reynolds numbers thereby suggesting the possible importance of vortex-wave interaction theory in turbulent shear flows. The relevance of the work to more general shear flows is also discussed.